The method : a thriller - Quirk, Matthew (William Morrow, an imprint of HarperCollins Publishers, 2026)
"Actress Anna Vaughn is fearless-on screen, at least. She tends to play doomed brunettes with a badass streak, and has put in countless hours training for parts and learning how to fight, shoot, and drive like a pro. She likes to believe she is as tough as her characters, but off-camera she leads a far quieter life: trying to keep her acting career alive so she can take care of her younger sister. When her best friend Natalie, her rock, disappears after a night out with a mysterious new man, the signs point to foul play and a circle of spies operating in Manhattan. Anna must use all the tricks she's learned for her roles to hunt for her missing friend. She quickly learns the dangers are all too real. She crosses paths with Kevin Matthews, an FBI agent on the same trail, tracking a string of killings and disappearances and a powerful clique of oligarchs. With Matthews as her handler, she has only days to prepare for the greatest performance of her life-going undercover. She will follow in her friend's footsteps through the gilded mansions, yachts, and secret clubs of New York to infiltrate the conspiracy and bring Natalie home. As the killers close in, her only chance for survival is to become as lethal as the characters she once played"--